Ginzburg-Landau system of complex modulation equations for a distributed nonlinear-dispersive transmission line (Neliniini Kolyvannya, 2006)
This work is devoted to investigation of nonlinear transmission line containing nonlinearcapacitors. In the work we study the stability of a set of 2 coupled Ginzburg-Landau (GL) equations derivedfrom a model of nonlinear transmission line. After deriving the main differential equation for the voltage,we consider an expansion of the voltage amplitudes for 2 travelling waves and obtain the time and spaceGinzburg-Landau differential equations for these amplitudes. We next study the existence and stability ofthe modulated amplitude waves in the complex plane, and show the existence of solition-like solutions.